Cost‐effectiveness of asthma clinic approach in the management of chronic asthma in Australia - Vittal Mogasale; Theo Vos (Elsevier, 2013)
Abstract Objectives: To compare cost‐effectiveness of an asthma clinic that would provide education, promotion of self‐monitoring of symptoms, regular review of treatment by a medical practitioner and a written asthma action plan to current practice in Australia. Methods: A decision tree model was used to compare treatment and improved management using asthma clinics under three scenarios: 1) intervention reduces only emergency department visits; 2) in addition, it leads to a reduction in days out of role; and 3) it also reduces unplanned general practitioner visits and hospitalisations. Evidence from existing published studies was used for asthma incidence, duration, treatment practices and health seeking behaviours. Costs for one year were estimated based on an asthma clinic trial in Australia. Results: The estimated $274 million annual cost of asthma clinics is much greater than the potential cost savings of $11 million resulting from reduced emergency department visits, and an overall potential cost saving of $85 million resulting from decreased GP visits and hospitalisations. The incremental cost‐effective ratio (ICER) is $24,000 if a reduction in days out of role is quantified as a health benefit in estimating disability‐adjusted life years (DALY). If a potential $85 million in cost‐savings from decreased emergency department visits, GP visits and hospitalisation is taken into account, the ICER drops to $17,000 per DALY averted. Conclusions: An asthma clinic as an intervention for improving self‐management may be cost‐effective in Australia if multiple benefits can be achieved. Implications: A large‐scale asthma clinic trial and long‐term evaluation of benefits are necessary to obtain stronger evidence on the benefit of asthma clinic approach in Australia.